A New Polar Ring Galaxy Discovered in the COSMOS Field. (1st September 2022) - Nishimura, Minoru; Matsubayashi, Kazuya; Murayama, Takashi; Taniguchi, Yoshiaki
Abstract: In order to understand the formation and evolution of galaxies fully, it is important to study their three-dimensional gravitational potential for a large sample of galaxies. Since polar-ring galaxies (PRGs) provide useful laboratories for this investigation, we have started our detailed study of a sample of known PRGs by using the data set obtained by the Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP). During the course of this study, we have discovered a new PRG, identified as SDSS J095351.58+012036.1. Its photometric redshift is estimated as z ∼ 0.2. The polar ring structure in this PRG appears to be almost perpendicular to the disk of its host galaxy without any disturbed features. Therefore, this PRG will provide us with useful information on the formation of such an undisturbed polar structure. We discuss its photometric properties in detail.